2020
DOI: 10.1080/87565641.2020.1764566
|View full text |Cite
|
Sign up to set email alerts
|

How Is Temporal Processing Affected in Children with Attention-deficit/hyperactivity Disorder?

Abstract: We compared the performance of children with ADHD and typically developing children on two temporal tasks, a bisection task and a reproduction task, in auditory and visual modalities. Children with ADHD presented a larger variability when performing auditory and visual temporal tasks. Moreover, they overestimated the durations in bisection tasks and underproduced duration intervals in the visual reproduction task. In the context of the pacemaker-accumulator model, these results suggest that temporal deficits m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…According to a review by Toplak et al (2006), most of the studies suggested timeprocessing alterations in ADHD in the form of higher discrimination thresholds or more discrepant reproductions (typically underestimations). Consistent with these findings, a recent study reported greater difficulties in discrimination between short and long time stimuli as well as under-reproduced time intervals in children with ADHD ( Suarez et al, 2020 ). According to Carelli and Wiberg ( 2012 ), such impairments are found in studies with duration discrimination or duration reproduction but not in verbal time estimation.…”
Section: Introductionsupporting
confidence: 63%
“…According to a review by Toplak et al (2006), most of the studies suggested timeprocessing alterations in ADHD in the form of higher discrimination thresholds or more discrepant reproductions (typically underestimations). Consistent with these findings, a recent study reported greater difficulties in discrimination between short and long time stimuli as well as under-reproduced time intervals in children with ADHD ( Suarez et al, 2020 ). According to Carelli and Wiberg ( 2012 ), such impairments are found in studies with duration discrimination or duration reproduction but not in verbal time estimation.…”
Section: Introductionsupporting
confidence: 63%
“…Currently, our research group studies the differential expression of ncRNA in subjects with Alzheimer's disease compared to healthy subjects. We also plan to study the exosomal load in patients with attention deficit-hyperactivity disorder [359][360][361][362][363][364] and HIV and Huntington's disease [365,366]. Funding: This study was financed by MINCIENCIAS, project "Nuevos ARN no codificantes exosomales y su papel en la patogénesis de la Enfermedad de Alzheimer", code 121584468097, grant 844/2019, contract 416-2020, awarded to Grupo en Genética y Medicina Molecular and Grupo de Productividad y Competitividad, Universidad del Norte, Barranquilla, Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that future genetic studies of ADHD may greatly benefit from our findings. In fact, such studies could use the severity of symptoms to elucidate how individuals with symptoms in different domains-inattention, hyperactivity, impulsivity-perform neuropsychological tasks (i.e., measures of working memory, cognitive function, and executive function) (Jimenez-Figueroa et al, 2017;Pineda-Alhucema et al, 2018;Suarez et al, 2020), and to determine the contribution to ADHD severity of genetic variants that confer susceptibility in Caucasian populations (Demontis et al, 2019). Although these candidate variants have not been replicated in genome-wide analyzes, their utility as risk variants for ADHD needs further investigation.…”
Section: Discussionmentioning
confidence: 99%